Pengaruh Efektivitas Program Keluarga Harapan dalam Menangulangi Kemiskinan di Kabupaten Aceh Barat - Afrida, Yulia; Badli, Saiful; Putra , T. Remi Ilham (Medan Resource Center, 2023)
This study aims to determine the effect of the effectiveness of the family hope program in overcoming poverty in West Aceh District. Based on the results of the research, it shows that the Effectiveness of the Family Hope Program (PKH) in Reducing Poverty in West Aceh Regency, the biggest expenditure of the population in West Aceh Regency is food consumption of IDR 1,200,000 per month. After that, the second largest consumption is non-food consumption in the form of education, which is IDR 600,000. This amount represents school fees in the form of snacks for children at school and photocopying costs. Followed by a medical fee of Rp. 350,000.00. This amount is calculated based on the minimum contribution required for certain BPJS participants. Then for other expenses in the form of electricity and water in the amount of Rp. 250,000.00 with details of electricity Rp. 100,000.00, for gallons of drinking water Rp. 70,000.00 and PDAM water Rp. 80,000.00. And the lowest consumption is clothing consumption of IDR 150,000. According to interview results, this is because most people buy clothes once a year, namely during Eid al-Fitr or at certain times such as weddings. While the results of the questionnaire answers (questionnaire) from 99 informants it could be concluded that the obstacle to the effectiveness of the Family Hope program in West Aceh District was the inaccuracy of PKH beneficiary targets caused by the determination of PKH beneficiaries not by the Regional Government of West Aceh District, but by the central government. So the data is not appropriate.